2019
DOI: 10.18203/2349-2902.isj20190384
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of Centchroman, Tamoxifen and Danazol in management of cyclical mastalgia

Abstract: Background: Mastalgia is a common problem and 60-70% women encounter it at least once in their lifetime. Many drugs have been used and are been used with varying response, like Tamoxifen, Danazol, primrose oil, topical analgesics and recently Centchroman. The objective of the present study was to compare the three most commonly used drugs in the treatment of mastalgia, namely Centchroman, Tamoxifen and Danazol with a placebo.Methods: All consecutive female patients more than 25 years of age with history of mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
2
0
0
Order By: Relevance
“…Almost similar observation was seen in some previous study by Rajswaroob et al 17 and Neogi P et al 21 and Nirhale et al 8 There are some limitations of our study. This study was performed in a single tertiary care hospital among small available population size.…”
Section: Discussionsupporting
confidence: 88%
“…Almost similar observation was seen in some previous study by Rajswaroob et al 17 and Neogi P et al 21 and Nirhale et al 8 There are some limitations of our study. This study was performed in a single tertiary care hospital among small available population size.…”
Section: Discussionsupporting
confidence: 88%
“…In this case, a single patient occasionally complained of several adverse symptoms. In several earlier research by Rajswaroob et al [18] , Neogi et al [19] and Nirhale et al [20] , a nearly same observation is made. In our study, the reported side effects due to Primrose use were comparable to Mostary et al [21] who reported bloating in 6.7% and headache in 2.2% of patients treated with primrose.…”
Section: Discussionsupporting
confidence: 65%